Simple design of masonry infilled reinforced concrete frames for earthquake resistance - Kalman Šipoš, Tanja (2019)
The extensive use of reinforced concrete frames with masonry infill and national and European regulations, which often neglect the influence of infill, has been identified as a field of research. The reliability of a numerical model with an equivalent diagonal for the parametric analysis of model buildings was tested using various experiments with one-story, one-bay and multi-storey, multi-bay infilled frames. Variability of parameters was simplified by classifying components based on material strength (masonry infill) and the coefficients of longitudinal reinforcement (reinforced concrete frame). The number of storeys, area ratio of infilled frame area in relation to the floor area (ρ), and the variability of ground acceleration as a measure of earthquake loading were investigated. The results show increased contribution to damage with increased number of storeys, decreased compressive strength of masonry infill, reduced longitudinal reinforcement ratio of columns, reduced area ratio, and increased peak ground acceleration (PGA) value. In the numerical model, area ratio ρ was observed to have significant importance and thus the minimum value of area ratio was defined. The study resulted in method, which enables simple design of infilled frames. Based on the classification (masonry infill, peak ground acceleration, number of storeys) minimum infilled frame area ratio can be determined and according to calculation of real area ratio for observed building can be compared in order to infilled frame building achieve acceptable behaviour under possible earthquake event.